Physical Layer Security Communications and Path Planning For UAV Base Stations - Niu, Guanchong; Cao, Qi; Pun, Man-On (Wireless and Optical Communication Conference, 2023)
Unmanned aerial vehicles (UAVs) have been recognized as the possible revolution in the fifth-generation (5G) wireless networks. In this work, we consider a scenario where a UAV base station (UAVBS) communicates with legitimate user equipments (UEs) in the presence of eavesdroppers (EDs). Specifically, a UAVBS travels around UEs in turns to send commands and collects information from UEs. To guarantee the data transmission rate, the millimeter-wave (mmWave) communication is integrated into the UAVBS system. Two problems are mainly resolved for the proposed system, namely radar-aided beamforming design and physical layer security (PLS) problem. With the assistance of the radar equipped on the UAVBS, the location of the UEs can be obtained before the beamforming is designed to solve the beam selection problem. In addition, the power allocation is optimized using the difference-of-two-convex-function (D.C.) programming algorithms. In order to safeguard data transmissions against such EDs, the PLS communication system is proposed by considering the location of the UAVBS. We derive the path planning algorithm for the UAVBS to avoid the data transmission with the EDs using the disciplined convex and concave programming (DCCP) algorithm. Extensive computer experiments validate the effectiveness of our proposed location-aware PLS communications in the UAVBS system.